2017
DOI: 10.1016/j.hbrcj.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pile parameters on the factor of safety of piled-slopes using 3D numerical analysis

Abstract: Slope stability can be achieved using different methods. Piles are commonly used to stabilize slopes or to improve slope stability. Stabilized slopes with piles are numerically studied in the current paper. A 3 dimensional (3D) finite element study is carried out to investigate the effect of different parameters on the stability of slopes stabilized with piles. A 3D finite element model was developed using the finite element program PLAXIS. The 3D model was verified using experimental data from the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The variation pattern of k y shown in Figure is consistent with the results obtained by Ito et al , Hassiotis et al , and Ashour and Ardalan . The dependence of failure mode on pile location was also found by Li et al and Abdelaziz et al by using the numerical analysis, and similar observations had been presented.…”
Section: Effect Of Pile Locationsupporting
confidence: 90%
See 1 more Smart Citation
“…The variation pattern of k y shown in Figure is consistent with the results obtained by Ito et al , Hassiotis et al , and Ashour and Ardalan . The dependence of failure mode on pile location was also found by Li et al and Abdelaziz et al by using the numerical analysis, and similar observations had been presented.…”
Section: Effect Of Pile Locationsupporting
confidence: 90%
“…Theoretically, piles can be installed into a slope vertically or with inclination, but inclined piles are used very few in practice. Abdelaziz et al studied the effects of pile inclination (and some other parameters including pile position, pile length, and pile diameter) on the factor of safety of piled slopes using 3D numerical analysis. They found that vertical piles give lower factor of safety than inclined piles, but the difference is considerably small.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of using such a system can be quantified by using different methods of slope stability analysis, such as limit equilibrium methods (LEM), bidimensional finite elements methods (2D FEM) or tridimensional finite elements methods (3D FEM). All types of approaches have advantages and disadvantages, but it was showed that using a 3D method gives more insight into the complex task of modelling the real behaviour of a slope consolidated with piles [4]. Introducing piles inside the soil domain of analysis considerably increases the difficulty of the problem, as it opens the door for other important aspects such as: interaction between the piles and the soil, slope geometry, piles position, the modelling approach of the piles, constitutive model adopted and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The Plaxis 3D, a specialized three-dimensional finite element analysis computer program for analysing soil stresses and deformation was used to develop the 3D finite element model [7]. It has features to handle the critical parameters of complex geotechnical engineering structures [8,9]. Among the constitutive models used in Plaxis 3D are the Mohr-Coulomb model (MC), the hardening soil model (HSM) and the hardening soil model with small-strain stiffness model.…”
Section: Introductionmentioning
confidence: 99%